Digital crime and forensic science in cyberspace - Kanellis, Panagiotis 1967- (Idea Group Pub., 2006)
"Digital forensics is the science of collecting the evidence that can be used in a court of law to prosecute the individuals who engage in electronic crime"--Provided by publisher.